2020
DOI: 10.4103/ijn.ijn_271_19
|View full text |Cite
|
Sign up to set email alerts
|

A case of intra-abdominal abscess due to sphingomonas paucimobilis in a patient on peritoneal dialysis: A case report and review of literature

Abstract: Sphingomonas paucimobilis is an aerobic gram-negative bacillus, widely distributed in the water and soil. It has also been found in nosocomial environments causing nosocomial infections. S. paucimobilis is a rare cause of peritoneal dialysis (PD)-related peritonitis. Here, we report the 14 th case, with a literature review. Our case is unique as this is the first reported case of intra-abdominal abscess associated with S. paucimobilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…3 Various case reports showing different infection sites of this organism are documented in literature like a splenic abscess, meningitis, osteomyelitis, secondary septic arthritis, bacteremia with septic pulmonary emboli, intra-abdominal abscess in a patient undergoing peritoneal dialysis, bacteremia outbreak in dialysis room among those using a common dialysis catheter, and paucimobilis fulminant keratitis. 2,[5][6][7][8][9][10] This case report is the second case of splenic abscess by S. paucimobilis documented in the literature, and probably the first case report of such an abscess in an immunocompetent host. The strain identified in the blood culture is susceptible to piperacillin/tazobactam, ceftriaxone, cefepime, imipenem, meropenem, amikacin, ciprofloxacin, and tigecycline.…”
Section: Discussionmentioning
confidence: 67%
“…3 Various case reports showing different infection sites of this organism are documented in literature like a splenic abscess, meningitis, osteomyelitis, secondary septic arthritis, bacteremia with septic pulmonary emboli, intra-abdominal abscess in a patient undergoing peritoneal dialysis, bacteremia outbreak in dialysis room among those using a common dialysis catheter, and paucimobilis fulminant keratitis. 2,[5][6][7][8][9][10] This case report is the second case of splenic abscess by S. paucimobilis documented in the literature, and probably the first case report of such an abscess in an immunocompetent host. The strain identified in the blood culture is susceptible to piperacillin/tazobactam, ceftriaxone, cefepime, imipenem, meropenem, amikacin, ciprofloxacin, and tigecycline.…”
Section: Discussionmentioning
confidence: 67%
“…There are seven references for case reports and literature reviews included in our study ( Figure 2 ) [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. We analyzed all the references cited in these seven references.…”
Section: Resultsmentioning
confidence: 99%
“…When the literature review was not clearly systematized, we considered only the case report of the study [ 42 ]. We retrieved for further analyses 89 cases from the seven case reports and literature review references [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. After screening the rest of the 42 references, we retrieved 358 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Ventilation pneumonia, [ 14 ] adenitis, myositis, [ 15 ] urinary tract infections, acute enteritis, [ 16 ] and abdominal abscesses associated with peritonitis have also been reported. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ventilation pneumonia, [14] adenitis, myositis, [15] urinary tract infections, acute enteritis, [16] and abdominal abscesses associated with peritonitis have also been reported. [17] In only 1 case published in 1987, S paucimobilis was identified in a splenic abscess associated with sepsis caused by Clostridioides difficile. [18] Our literature research reported no other case report of splenic abscess caused by S paucimobilis.…”
Section: Discussionmentioning
confidence: 99%